Antibody biomarkers in CNS demyelinating diseases – a long and winding road. (24th May 2015) - Berger, T.; Reindl, M.
<x xml:space="preserve">Abstract</x> Over several decades, studies sought potential markers to diagnose and to predict the clinical course of central nervous system (CNS) demyelinating disorders, especially in multiple sclerosis, acute disseminated encephalomyelitis and neuromyelitis optica spectrum disorders. Reliable biomarkers would ensure correct diagnoses, determine future disease evolvements, stratify patients for appropriate treatments and monitor disease activity and treatment effects – in summary, meet the longing for personalized medicine in these diseases. Out of a plethora of potential biomarker candidates antibodies have turned (again) into the scientific focus, due to pivotal immunological and neuropathological findings in the past 20 years. A major breakthrough and stimulus for further research was the identification of anti‐aquaporin‐4 antibodies in neuromyelitis optica. Various other myelin and non‐myelin antigens were investigated in detail for diagnostic and prognostic purposes, such as antibodies to myelin oligodendrocyte glycoprotein or to the potassium channel KIR4.1. Further, the use of biopharmaceutical treatments in multiple sclerosis led to intense research activities to identify anti‐treatment neutralizing antibodies and their clinical consequences. This review briefly summarizes the current knowledge on antibodies in the diagnosis, prognosis, disease and treatment monitoring of CNS demyelinating disorders.